Predictors of adherence to antiretroviral therapy among human immunodeficiency virus patients in Jos University Teaching Hospital, Nigeria - Panmial, P. D.; Ismail, Suriani; Abdul Manaf, Rosliza; Md Said, Salmiah; Agbaji, O. (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Sustained optimal adherence to antiretroviral therapy (ART) is required for long-term suppression of viral replication. However, adherence level in Jos, Nigeria has been reported to be below optimal adherence, thus this study investigates the predictors of adherence to antiretroviral therapy among Human Immunodeficiency Virus (HIV) patients there. Methods: A validated and pretested questionnaire was used in this cross-sectional study to collect data on sociodemographic characteristics, duration of being on ART, alcohol consumption, presence of symptoms, drug type and disclosure status from 224 randomly selected adult HIV patients. Chi-square and binary logistics regression were used for data analysis. Level of significance was set at 0.05. Results: Only 14.3% of the respondents had optimal adherence. Adherence to ART is significantly associated with gender (p = 0.043), duration of ART use (p = 0.041), alcohol (p = 0.029), drug type (p = 0.001), and disclosure status (p = 0.004). Binary logistics regression reveals that females are 2.4 times more likely to have optimal adherence than males, patients on ART for over 10 years are 2.5 times more likely to have optimal adherence than those less than 10 years, and patients with disclosed HIV status are 3.3 times more likely to have optimal adherence than those who had not. Conclusion: Generally, the patients had suboptimal adherence. Being female, having longer duration on ART and disclosure status are predictors for optimal adherence. Intervention with emphasis on males and new patients on ART is recommended to educate on optimal adherence and motivate patients to disclose their status.